Super Momism and Mothers’ Guilt: Experiences of Pakistani Working Women - Aysha Jawaid; Rabia Ali (Journal of Peace, Development and Communication, 2024)
This paper is drawn from the PhD dissertation of the first author. The larger study primarily focused on the mothering practices of Eastern supermoms following the contemporary ideology of new-momism. It also highlighted the emerging concept of transiting masculinities in Eastern societies and the effect of ruling relations between couples affecting women’s self-identity in contextualized institutional settings. Through these objectives, we were able to understand the urban culture of new momism and working mothers’ struggles to achieve the set normative standards of the perfect mother. In understanding this phenomenon in Pakistan and taking an interpretivist approach institutional ethnography (IE) was utilized as a method of inquiry to understand new-momism and its effect on women's self-identity by placing it in changing relations of ruling due to transformed masculinities. While the larger study yielded six themes; this paper focuses on one theme i.e. mother guilt and its impact on self-identity of the working women. The paper contributes to larger global discourses on new momism by presenting the experiences of Pakistani working mothers.